Understanding perception of the radiology community concerning virtual reality (VR) and augmented reality (AR) technology in radiology education - Suneet Paulson; Dwight Figueiredo; Sushant Matre (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Radiology education is crucial in developing the fundamental skills and knowledge for effectively interpreting medical images, planning interventions, and providing high-quality patient care. By incorporating immersive technologies like VR and AR, significant enhancements to preexisting radiology-based teaching and training simulations can enhance learning, visualization, and skill development in radiology. This paper explores four basic types of VR technology used in radiology education, which are non-immersive, semi-immersive, fully immersive, and augmented reality, and their applications. This review talks about the key applications of VR and AR to provide students with real-world training where students gain hands-on experience in a risk-free and controlled environment. Virtual radiography simulation can be used to practice and enhance patient positioning skills without getting exposed to any X-ray radiation. The VERT platform can be used to simulate radiography processes, including patient setup and dose planning. Furthermore, 3D VR simulation provides a detailed three-dimensional model of anatomical structures, enhancing learning. This review also focuses on the applications of AR, such as VIPER (virtual interactive patient education and radiotherapy) and ARTUR (augmented reality for radiographic training). While both VIPER and ARTUR are designed to improve learning and training in radiology, VIPER primarily focuses on patient education, offering a 3D visualization of the radiotherapy process, including treatment rooms, equipment, and patient anatomy. On the other hand, ARTUR is an application that utilizes holograms to provide a 3D image that students can manipulate to practice radiographic positioning. Conclusions Integrating VR and AR in radiology education can enhance qualities like learning, visualization, and skill development using interactive and risk-free simulations. Tools like VERT, 3D VR simulation, VIPER, and ARTUR provide users a sense of hands-on experience, transforming the traditional ways of teaching. This review talks in detail about the perception of learners and educators on VR and AR, along with the qualities and skills users can enhance using these technologies. The paper highlights key factors hindering the adoption of these technologies in radiology education.